PELAKSANAAN PENYELENGGARAAN HYGIENE SANITASI DAN PEMERIKSAAN KUALITAS AIR MINUM PADA DEPOT AIR MINUM ISI ULANG DI KOTA PADANG TAHUN 2012 - Dikri Abdilanov; wirsal hasan; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2013)
Hygiene Sanitation Implementation and Examination of Drinking Water Quality on Drinking Water Stands on Padang in 2012. Refill water was one of important water drinking resource used by people. In order to keep the water being safe therefor need a sanitation hygiene execution effort of drinking water stand.The Purpose of this research was to determine the execution of sanitation hygiene and nitrate level on drinking water stand. The method used in this research was observational and laboratory examination by used observation sheets and laboratory examination on 24 sample which selected by random sampling. The research was a survey and the result presented in a frequency distribution table.The result showed that 12 depot water stand (50%) was not qualified on drinking water stand sanitation hygiene. Most of drinking water stand was not qualified on internal supervision amounted 17 drinking water stand (70,8%). Almost all of drinking water stand was not qualified on licensing amounted 20 depot water stand (83,3%). 8 depot water stand (33,3%) was not qualified on microbiologic for drinking water. Nitrate level on basic and drinking water was qualified the nitrate level qualification. The conclusion of this research were most of drinking water stand not qualified for sanitation hygiene, internal supervision, and licensing. Some part of was not qualified on microbiologic then nitrate content was qualified at all samples of drinking water stand. There are recommended for the drinking water stand to executing sanitation hygiene. And, government should to implement external supervision then sanitation hygiene execution of drinking water stand would be good. Keywords: Sanitation, Supervision, Licensing, Water Quality